Pengaruh Financial Distress, Deferred Tax Expense Dan Debt Policy Terhadap Tax Avoidance - Melani, Nur De Afni; Ferdiansyah, Ferdiansyah (Politeknik Negeri Ambon, 2024)
One way to achieve tax retention is through tax avoidance, which is a legal reduction in the tax burden and avoids conflicts with tax regulations. This study aims to analyze the influence of financial distress, deferred tax expense and debt policy on tax avoidance. The sample used in this study was 9 property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the period from 2018 to 2022 using multiple linear regression using purposive sampling techniques. The data used in this study is secondary data in the form of financial statements from each company that has been used as a research sample. The results of this study show that Financial Distress has no effect on Tax Avoidance, Deferred Tax Expense has an effect on Tax Avoidance, Debt Policy has no significant effect on Tax Avoidance, and simultaneously Financial Distress, Deferred Tax Expense and Debt Policy have an effect on Tax Avoidance